MarR homologs with urate-binding signature - Perera, Inoka C.; Grove, Inoka C. (My University, 2010)
Abstract: Bacteria that associate with living hosts require intricate mechanisms to detect and respond to host defenses. Part of the early host defense against invading bacteria is the production of reactive oxygen species, and xanthine oxidase is one of the main producers of such agents. The end-product of the enzymatic activity of xanthine oxidase, urate, was previously shown to be the natural ligand for Deinococcus radiodurans-encoded HucR and it was shown to attenuate DNA binding by Agrobacterium tumefaciens-encoded PecS and Burkholderia thailandensis-encoded MftR, all members of the multiple antibiotic resistance regulator (MarR) family. We here show that residues involved in binding urate and eliciting the DNA binding antagonism are conserved in a specific subset of MarR homologs. Although HucR controls endogenous urate levels by regulating a uricase gene, almost all other homologs are predicted to respond to exogenous urate levels and to regulate a transmembrane transport protein belonging to either the drug metabolite transporter (DMT) or the major facilitator superfamily (MFS), as further evidenced by the presence of conserved binding sites for the cognate transcription factor within the respective promoter regions. These data suggest the use of orthologous genes for different regulatory purposes. We propose the designation UrtR (urate responsive transcriptional regulator) for this distinct subfamily of MarR homologs based on their common mechanism of urate-mediated attenuation of DNA binding.
Keywords: Urate; MarR; PecS; transcriptional regulation; ligand binding